CONGENITAL HEART DISEASE IN CHILDREN AND ADULTSSurgical correction of atrial septal defect in the elderly - Rudiene, Virginija; Gumbiene, Lina; Dranenkiene, Alicija; Karalius, Rimantas; Sirmenis, Raimondas; Tarutis, Virgilijus (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Atrial septal defects (ASDs) are one of the most common congenital malformations in adults. Correction of ASDs in advanced age remains controversial, even though beneficial effects in this patient group were found in recent studies. In older patients, less invasive transcatheter closure of ASDs has been recommended. Aim : The aim of this study was to analyze our advanced age ASD surgical cohort: early and late results. Material and methods: Retrospective analysis of 32 patients operated on at an age of ≥ 60 years (i.e. age 66.13 ± 4.8, range from 60 to 78) in our center between 2001 and 2011 was carried out. We reviewed our experience of surgical ASD closure in elderly patients over a 10-year period to assess the effects of this type of treatment on early postoperative and long-term survival, early and late complications, preoperative and postoperative clinical status (New York Heart Association [NYHA] functional class), pulmonary hypertension (PH) and atrial arrhythmias. The patients were divided into two groups according to age. Results: The frequency of comorbidities was lower in younger age group patients (11 [61%] vs. 13 [93%], p < 0.05). Atrial fibrillation/flutter was found in 21 (66%) of all patients. Late postoperative mortality was higher in the older patient group (3 [21%] vs. 1 [5.6%]). Despite this, we observed significant improvement of symptoms and functional ability in the older population after surgical ASD closure (group I, n = 10 [56%] vs. group II, n = 12 [86%]). Conclusions : Surgical correction of clinically significant ASD is effective even in older patients with comorbidities.